2013
DOI: 10.1038/srep02656
|View full text |Cite
|
Sign up to set email alerts
|

Atomic and electronic structure of an alloyed topological insulator, Bi1.5Sb0.5Te1.7Se1.3

Abstract: Bi2−xSbxTe3−ySey has been argued to exhibit both topological surface states and insulating bulk states, but has not yet been studied with local probes on the atomic scale. Here we report on the atomic and electronic structures of Bi1.5Sb0.5Te1.7Se1.3 studied using scanning tunnelling microscopy (STM) and spectroscopy (STS). Although there is significant surface disorder due to alloying of constituent atoms, cleaved surfaces of the crystals present a well-ordered hexagonal lattice with 10 Å high quintuple layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 40 publications
4
30
1
1
Order By: Relevance
“…The BSTS crystal cleaves along the (111) crystal plane and scanning tunnelling microscopy experiments have shown that the terminated plane has Te/Se atoms on it ref. 16.
Figure 1( a and b ) show the primitive and hexagonal unit cells of BiSbTeSe 2 respectively. The dotted box encloses the structure of five atomic layers which is called quintuple layer (QL).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BSTS crystal cleaves along the (111) crystal plane and scanning tunnelling microscopy experiments have shown that the terminated plane has Te/Se atoms on it ref. 16.
Figure 1( a and b ) show the primitive and hexagonal unit cells of BiSbTeSe 2 respectively. The dotted box encloses the structure of five atomic layers which is called quintuple layer (QL).
…”
Section: Resultsmentioning
confidence: 99%
“…Recently, quantum hall effect (QHE) 15 and scanning tunnelling spectroscopy (STS) 16 studies have been used to confirm the topological characters of BiSbTeSe 2 and Bi 1.5 Sb 0.5 Te 1.7 Se 1.3 . Tunability of the Dirac cone also has been observed in some of the compositions of Bi 2− x Sb x Te 3− y Se y by using angle resolved photoelectron spectroscopy (ARPES) measurements 17, 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering that STM image contains the contribution from local density of states (LDOS), the different brightness may be the result of electronic distortions caused by random substitution of Bi with Sb. It is similar to the surfaces of Bi 1−x Sb x alloy13, Bi 2+x Te x Se14 and Bi 1.5 Sb 0.5 Te 1.7 Se 1.3 15. The STS measurements were performed to investigate the electronic structures of BST.…”
Section: Resultsmentioning
confidence: 99%
“…Recent scanning tunneling microscopy and spectroscopy on our BSTS crystals showed that their surface states have linear dispersion and chirality from spin texture, thus verifying the topological nature. This implies that topological surface states remain intact even with alloying of constituent atoms and significant surface disorder [39].…”
Section: Experimental Methodsmentioning
confidence: 99%